CONCEPTUAL FRAMEWORK FOR THE EUROPEAN UNION’S CYBER SECURITY STRATEGY AND EU ACTIONS BEFORE STRATEGY DOCUMENT - EREN, Mehmet (Cyberpolitik Journal, 2016)
The subject of this article is the EU’s cyber security policy. Cyber security gets more important with advancements in information and communications technology. The article starts with a comprehensive explanation of cyber security. The conceptual framework of this article is securitization, a concept developed by the Copenhagen School, especially by Ole Wæver and Barry Buzan. Cyber-attacks on Estonia is examined as example of cyber attacks that directly affected the European Union. “Cybersecurity Strategy of the European Union” is the basis of the EU's cyber security policy. This article throughly examines the major goals and policies/actions that this strategy outlines. The major argument of this article that the process of setting up the EU Cyber security strategy can be explained by the securitization approach as the conceptual framework, and the pre-strategy actions of EU strengthen this argument.